Answer: x = 2, x = - 5
Explanation:
1) The given expression is not clear.
I will rewrite it using the math editor for better understanding
[tex]12^{x^2+5x-4}=12^{2x+6}[/tex]
2) Since the bases are equal, the exponents are equal too.
=> x^2 + 5x - 4 = 2x + 6
Solve that quadratic equation step by step:
3) transpose 2x + 6 to the left side:
x^2 + 5x - 4 - 2x - 6 = 0
4) Combine like terms:
x^2 + 3x - 10 = 0
5) Factor:
(x + 5) (x - 2) = 0
6) Equal each factor to 0
x + 5 = 0 => x = - 5
x - 2 = 0 => x = 2
Those are the solutions x = - 5 and x = 2